The colonial shock. Human’s tecnologies and border art - Piñeiro Aguiar, Eleder; Lorenzo Castiñeiras, Juan José (Nawi, 2021)
In this theoretical and interpretive text we develop a triangulation between a political art and the decolonial conceptualization around racism and border thinking. For this we analyze the works of various authors who have been working on otherness and put them in debate with a critique of Eurocentric capitalist modernity. As the backbone we have intercultural dialogue, travel practice, the technological uses of surveillance and control, and power relations towards subalternized populations. What we want to highlight is the importance of what we call colonial shock as a configurator of “other” proposals to understand the human line.